INVESTIGATION OF IMPURITIES PRESENT IN RECYCLING AND REUSING OF SCRAP LEAD FOR ACCUMULATOR INDUSTRY - Farooq, A.; Irfan, N.; Chaudhry, M. M.; Riaz, M.; Nawab, S. (The Nucleus, 2012)
Recycling and reusing are the basic strategies of reducing solid waste generated from industries. Millions of batteries containing toxic metals and poisonous wastes are discarded every year in Pakistan. Battery waste deposited in landfills increases the concentration of toxic metals in leachates obtained from landfill base. For this reason, recycling of locally available scrap lead has been focused. During reduction and refining stages, samples were obtained at various stages from a five ton lead smelting pot of an accumulator industry. Various impurities present were determined and removed in order to reuse in accumulators. X-ray fluorescence (XRF) and atomic absorption spectroscopy (AAS) techniques were used to analyze the samples obtained at various stages of recycling. This work has been carried out to reduce these impurities and the refining process has thus been optimized. The lead thus obtained is 99.98 % pure.